Agromorphologic, genetic and methylation profiling of Dioscorea and Musa species multiplied under three micropropagation systems - Jekayinoluwa, T.; Gueye, B.; Bhattacharjee, Ranjana; Osibanjo, O.; Shah, T.; Abberton, Michael T. (Public Library of Science, 2019)
Plant in vitro vegetative propagation using classical semi-solid culture medium is limited due to the low degree of automation, suboptimal nutrient availability and induced physiological stress which often reduce its efficiency. Temporary Immersion System (TIS) emerged as an innovative approach to optimize and eliminate the drawbacks associated with the conventional system of micropropagation. In this study, both Dioscorea and Musa spp. were subjected to conventional semi-solid culture media, complete immersion in shaking liquid culture media and TIS using RITA bioreactor. In vitro grown plantlets were screened for possible vegetative changes using agro-morphological descriptors while genetic and methylation differences were assessed using amplified fragment length polymorphism (AFLP) and methylation-sensitive amplification polymorphism (MSAP). In vitro results showed that the number of shoots produced in Musa spp. varied significantly (P≤0.001) with the type of culture system. The highest mean shoot produced was observed with TIS (28.40) and the least using semi-solid culture medium (1.13). For Dioscorea spp., there was no significant interaction between the hormone combination and the culture system. However, the lowest mean shoot value (1.55) was observed in the semi-solid culture medium. Genetic analysis via AFLP using 15 primer pair combinations revealed that the 3 culture systems maintained genetic variation for Musa and Dioscorea spp. under in vitro and field conditions. Results showed 99% and 91% of the total bands were polymorphic under in vitro and field conditions respectively for Musa and 100% polymorphism for Dioscorea under in vitro and field conditions. Methylation investigation via MSAP using 12 primer pair combinations showed 25% and 46% polymorphic methylated-sensitive loci, 100% and 78% of non-methylated loci of the total bands generated under in vitro and field conditions respectively. Unmethylated (HPA+/MSP+) levels were highest in TIS (0.0842) as compared to CI (0.0227) and SS (0.0161) while full methylation or absence of target (HPA-/MSP-) was lowest in TIS (0.5890) and highest in SS (0.7138). For Dioscorea, 52% and 53% methylated sensitive loci and 100% non-methylated loci were polymorphic under in vitro and field conditions respectively. Although in vitro plant tissue culture techniques led to methylation at some loci of both species, there were no observable changes in the phenotype of both crops under field conditions. This also confirmed that not all methylation events lead to phenotypic changes.